The Importance of Keeping Funeral Rituals during the Challenging Perod of the Covid-19 Pandemic - Horáčková, Kateřina; Podeszwa, Ondřej; Ifthikar, Moneeba; Sládek, Karel; Kopecký, Michal; Blanař, Vít; Hošek, Oldřich (My University, 2024)
Background: The article highlights the importance of the implementation of rituals associated with the end of life during the time of the COVID-19 pandemic, in particular pointing out the consequences resulting from failure to perform these rituals. Methods: Data were collected using a qualitative research design, as the chosen method was a personal case study. The selected technique was a semi-structured interview with five respondents. The entry criterion for the research was that participants had to be survivors who lost close relatives during the COVID-19 pandemic, either in a hospital or on the way to a hospital. The results were analyzed according to thematic analysis recommendations, using Atlas.ti software. Results: Research highlights the importance of performing the rituals associated with the end of life. Failure to perform these rituals poses a high risk of complicated grief. From the perspective of the bereaved respondents, a wide range of consequences were observed, particularly in the psychosocial, spiritual, and physical domains. Conclusion: The extent of the impact caused by the inability to perform these rituals can be so profound that it is not easily manageable without professional help and support. Psychosocial and spiritual support from professionals completely failed during the pandemic. Further research should focus on promoting the digitalization of healthcare and improving access to telecommunications/telemedicine. It should also address enhancing the expertise of healthcare workers and increasing information literacy among the older patient population. Additionally, research should be directed toward strategies for developing palliative care under challenging epidemiological conditions.
Důležitost dodržování pohřebních rituálů během pandemie COVID-19
Keywords: COVID-19; Rituals; End of life; Family; Dying